Measurement of in vitro inhibition by lactobacillus spp. Against salmonella Heidelberg - Domingos, I.; Vellano, I. H.B. [UNESP]; Moraes, A. C.I. [UNESP]; Altarugio, R. [UNESP]; Filho, R.L. Andreatti [UNESP]; Okamoto, A. S. [UNESP] (My University, 2018)
Background and Objective: Salmonella Heidelberg is considered to be a microorganism of great concern in the poultry industry, since it causes losses for farmers and is a great risk to public health. Brazil stands out worldwide regarding poultry exports and because of this, researchers have increasingly been trying to reduce the incidence of this pathogen, mainly through taking care of the intestinal health of the birds. A healthy intestinal microbiota comprises many microorganisms and among them, Lactobacillus spp. is noteworthy given that studies have already proven its effectiveness in inhibiting several pathogenic microorganisms in vitro. The objective of the present study was to correlate the results obtained using two methods for measuring antagonist activity between Lactobacillus spp. And Salmonella Heidelberg and to observe whether the correlation between the two methods tested was positive or negative. Methodology: Ten strains of Lactobacillus spp. were used and these showed positive results regarding inhibition of Salmonella Heidelberg, both in the Spot on the Lawn test and in the concomitant culture. The two tests were carried out to measure the inhibitory capacity of Lactobacillus spp. on Salmonella Heidelberg, by correlating the size of the inhibition halo obtained in the Spot on the Lawn test with the Salmonella Heidelberg count in the concomitant culture. Results: It has been observed that Lactobacillus spp. have a great capacity of inhibition against Salmonella Heidelberg. However, this capacity varies according to the strain of Lactobacillus spp., in addition, other factors may also influence this ability as the temperature, the culture medium and the time of exposure between the samples. Conclusion: Although all Lactobacillus spp. inhibit Salmonella Heidelberg, it was not possible to correlate the data obtained, since each Lactobacillus spp. presented a halo measurement that did not correspond to the quantity of Salmonella Heidelberg actually inhibited, due to other factors involved.
Keywords: Antagonism; Chicken; Microbiota; Pathogen inhibition; Probiotic